E. H. Carr and Hans Morgenthau: "Heresy" in the Realist Camp (Czech Journal of International Relations, 2006)
This article first disputes the traditional view of Realist School ofinternational relations as inherently positivistic, and second presents areaction to the polemic taking its course in pages of this journal betweenMarek Loužek and Petr Drulák. In the first part, those aspects of the work ofE. H. Carr and Hans Morgenthau that challenge their placing in thepositivist camp are presented. In the second part, these remarks are usedas a critique of Marek Loužek's schematic division of theories ofinternational relations as between normativist idealism and positivistrealism.
Keywords: Realism; epistemology; E. H. Carr; H. Morgenthau; positivism